Microgravity and the intervertebral disc: The impact of space conditions on the biomechanics of the spine - Marfia, Giovanni; Guarnaccia, Laura; Navone, Stefania Elena; Ampollini, Antonella; Balsamo, Melissa; Benelli, Francesca; Gaudino, Chiara; Garzia, Emanuele; Fratocchi, Claudia; Di Murro, Claudia; Ligarotti, Gianfranco Kim; Campanella, Carmelo; et al. (Frontiers in Physiology, 2023)
The environmental conditions to which astronauts and other military pilots are subjected represent a unique example for understanding and studying the biomechanical events that regulate the functioning of the human body. In particular, microgravity has shown a significant impact on various biological systems, such as the cardiovascular system, immune system, endocrine system, and, last but not least, musculoskeletal system. Among the potential risks of flying, low back pain (LBP) has a high incidence among astronauts and military pilots, and it is often associated with intervertebral disc degeneration events. The mechanisms of degeneration determine the loss of structural and functional integrity and are accompanied by the aberrant production of pro-inflammatory mediators that exacerbate the degenerative environment, contributing to the onset of pain. In the present work, the mechanisms of disc degeneration, the conditions of microgravity, and their association have been discussed in order to identify possible molecular mechanisms underlying disc degeneration and the related clinical manifestations in order to develop a model of prevention to maintain health and performance of air- and space-travelers. The focus on microgravity also allows the development of new proofs of concept with potential therapeutic implications.